Effect of low and high doses of Salmonella enteritidis PT4 on experimentally infected chicks - Asheg, A A; Fedorová, V; Pistl, J; Levkut, M; Revajová, V; Kolodzieyski, L; Sevcíková, Z; Pilipcinec, E (Folia microbiologica, 2001)
Chicks (1-d-old, three groups, each containing 50 chicks) were inoculated with 2 x 10(2) and 2 x 10(8) CFU of Salmonella enteritidis; the third group were kept as uninoculated control. Five birds from each group were euthanized at intervals from 6 h to 4 weeks post-inoculation (pi). In the low-dose group S. enteritidis was isolated from 60% cecal samples at 18 h pi, and from 20% of livers at 3 d pi. Individual variation in the frequency of S. enteritidis recovery was observed in this group. The clearance of salmonella from the organs was faster in the low-dose group, and salmonella was not isolated from the liver and cecum at 21 and at 27 d pi, respectively. However, in the high-dose group, S. enteritidis was isolated from all ceca and 80% of liver 6 h pi, and salmonella was detected in the cecum and liver throughout the experiment. Serous typhlitis and unabsorbed yolk sac were the most prevalent lesions in both groups. Granulomatous nodules in the cecum were found occasionally in some cases in both inoculated groups, which can play a role as reservoirs in carrier chicks.
Keywords: žloutkový vak; Liver; játra; cékum; Time Factors; Salmonella enteritidis; virulence; Bird Diseases; kur domácí; Animals; Chickens; nemoci ptáků; zvířata; Virulence; časové faktory; Cecum; salmonelová infekce u zvířat; Salmonella Infections, Animal; Yolk Sac